Synthesis and structure of tetraethynylsilane and its silylated derivatives - Geyer, Florian Ludwig; Rominger, Frank; Bunz, Uwe H. F. (Chemistry - a European journal, 2014)
The known tetrakis((trimethylsilyl)ethynyl)silane was prepared and deprotected. By using trifluoromethanesulfonic acid, the smooth stepwise desilylation of the starting material was achieved, and all of the partially protected and the fully deprotected species were isolated by sublimation. Crystal structures of all of the partially and the fully deprotected species were obtained. None of the compounds is thermally sensitive. Attempts to explosively decompose these species upon heating failed.
Gesehen am 31.07.2020